No War, No Peace - Ginty, Roger Mac. author. aut Link
XII, 230 p.
Keywords: This book investigates stalled and dysfunctional peace processes and peace accords in societies experiencing civil wars. Using a critical and comparative perspective, it offers strategies for rejuvenating and re-orientating stalled peace processes and peace accords so that they are more able to foster sustainable and inclusive peace.